Incoherence and incompatibility in planning law. Issue 2 (13th July 2015) - Lees, Emma; Shepherd, Edward
Abstract : Purpose: – The purpose of this paper is to analyse the obligations imposing localism and the presumption in favour of sustainable development in English planning law. Design/methodology/approach: – The paper uses doctrinal analysis to examine section 38 PCPA 2004 and the NPPF to assess whether the obligations are coherent when considered as stand-alone obligations, and whether they are compatible when combined. Case law and the statutory provisions are examined to assess this. Planning theory is also examined to bring a multidisciplinary focus to the analysis. Findings: – The paper concludes that there are problems with these legal obligations when considered as stand-alone obligations. There is imprecision over the meaning of key terms; the "presumptions" established do not operate as true presumptions; and there is an ambiguity as to the hierarchy of norms and the allocation of decision-making control. When combined, the incoherence increases. It is argued that this occurs thanks to underlying disagreements in key concepts in planning theory. Originality/value: – This paper examines the new structures of planning law introduced under the Localism Act 2011 and the NPPF and considers how this structure works in practice. It does so from the multidisciplinary viewpoint of planning law and planning theory and links these two approaches. This is not replicated elsewhere in the literature. It considers in detail the ensuing case law, and the contradictions that appear. Again, there is little surveying the overall framework of planning law in the UK.